Avoidable environmental disasters and infant health: Evidence from a mining dam collapse in Brazil. (2nd September 2020) - Carrillo, Bladimir; Da Mata, Daniel; Emanuel, Lucas; Lopes, Daniel; Sampaio, Breno
Abstract: We study the health consequences of one of the largest environmental disasters of the world mining industry, which largely stemmed from regulatory failure. Exploiting the timing and location of the Mariana mine tailings dam collapse in Brazil, we show that in utero exposure to the tragedy significantly reduced birth weight and increased infant mortality. The adverse effects were stronger for infants born to less educated and nonmarried mothers. These findings indicate that poorly enforced environmental regulation may have long‐term welfare impacts on local communities.